Nonenhancing Intramedullary Astrocytomas and Other MR Imaging Features: A Retrospective Study and Systematic Review - Seo, H.S. (AJNR Am J Neuroradiol, 2010)
BACKGROUND AND PURPOSE: Most intramedullary astrocytomas have been known to exhibit at least some enhancement on MR imaging regardless of cell type or tumor grade. The purpose of this study was to evaluate the incidence of nonenhancing intramedullary astrocytomas through a retrospective study within our institutions and a systematic review of the medical literature. MATERIALS AND METHODS: A total of 19 consecutive patients (male to female ratio, 11:8; mean age, 27.84 ± 19.0 years) with primary intramedullary astrocytomas (3 WHO grade I, 13 WHO grade II, 3 WHO grade III) who underwent preoperative MR imaging with contrast enhancement were included in this retrospective study from 4 institutions. The tumor-enhancement patterns were classified into the following categories: 1) no enhancement, 2) focal nodular enhancement, 3) patchy enhancement, 4) inhomogeneous diffuse enhancement, and 5) homogeneous diffuse enhancement. Seven articles including MR imaging enhancement studies of intramedullary astrocytomas were eligible for literature review. RESULTS: In the retrospective study, 6 astrocytomas (32%), including 2 anaplastic astrocytomas, did not enhance at all. Focal nodular enhancement was identified in 5 astrocytomas (26%); patchy enhancement, in 3 (16%); inhomogeneous diffuse enhancement, in 5 (26%); and homogeneous diffuse enhancement, in none. In the literature review, the frequency of nonenhancing intramedullary astrocytomas was 14 of 76 (18%), including 2 anaplastic astrocytomas. CONCLUSIONS: Nonenhancing intramedullary astrocytomas are not uncommon and comprise between 20% and 30% of intramedullary astrocytomas. Therefore, astrocytoma must remain in the differential diagnosis of nonenhancing intramedullary lesions, particularly if the lesion demonstrates a prominent mass effect or cord expansion.